Process Network Modularity, Commonality, and Greenhouse Gas Emissions - Dooley,Kevin; Pathak,Surya; Kull,Thomas; Wu,Zhaohui; Johnson,Jon; Rabinnovich,Elliot (Journal of Operations Management, 2019)
Keywords: Supply Chain

Performance Based Contracting in the Defence industry: Exploring Triadic Dynamics between Government, OEMs and Suppliers. - Howard,Mickey; Wu,Zhaohui; Caldwell,Nigel; Jia,Fu; König.,Christian (Industrial Marketing Management, 2016)
Keywords: Supply Chain

Produce Supply Chain Management: Two Tales in One City - Wu,Zhaohui; Christensen,Kurt (2011)
It is a teaching case in a book.
Keywords: Supply Chain